Association Between Residence Status Regularization and Access to Healthcare for Undocumented Migrants in Switzerland: A Panel Study - Fakhoury, Julien; Burton-Jeangros, Claudine; Consoli, Liala; Duvoisin, Aline; Jackson, Yves (Frontiers in Public Health, 2022)
Revised version of the abstract in the revised manuscript. Due to changes requested by Reviewers, the abstract is 389 words long.